Polyhistor : studies in the history and historiography of ancient philosophy : presented to Jaap Mansfeld on his sixtieth birthday - Mansfeld, Jaap.; Algra, Keimpe, 1959-.; Horst, Pieter Willem van der.; Runia, David T. (Philosophia Antiqua, 1996)
During the past three decades Jaap Mansfeld, Professor of Ancient Philosophy in Utrecht, has built up a formidable reputation as a leading scholar in his field. His work has concentrated on the Presocratics, Hellenistic Philosophy, the sources of our knowledge of ancient philosophy (esp. doxography) and the history of scholarship. In honour of his sixtieth birthday, colleagues and friends have contributed a collection of articles which represent the state of the art in the study of the history of ancient philosophy and frequently concentrate on subjects in which the honorand has made important discoveries. The 22 contributors include M. Baltes, J. Barnes, J. Brunschwig, W.M. Calder III, J. Dillon, P.L. Donini, J. Glucker, A.A. Long, L.M. de Rijk, D. Sedley, P. Schrijvers, and M. Vegetti. The volume concludes with a complete bibliography of Jaap Mansfeld's scholarly work so far.